INNOVATIVE APPROACHES TO ENZIMIZATION OF LEATHER PRODUCTION - KOPYTINA, IRYNA; ANDREYEVA, OLGA; MOKROUSOVA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Genuine leather production, which involves the use of a wide range of chemicals and is accompanied by the formation of a significant amount of waste, remains a difficult area for the creation and application of cleaner technologies. To replace harmful chemicals, you can use enzymes, which are natural substances that are safe for the environment. At the same time, from an economic point of view, it is practiced to use not the enzymes themselves, but their preparations, however, all the same, the cost of their use remains high, as the cost of raw hides and other reagents used for its processing remains increasingly high. This creates new problems for the industry. Therefore, for the sustainable development of the leather industry towards the production of competitive products, resource saving and greening of production, it is necessary to look for, develop and implement effective innovative approaches to improving the technology of leather manufacturing, including through the wider use of enzymatic processes. As a result of the analysis of modern research in the field of enzymization of leather production, innovative approaches to the use of commercially available and new enzyme preparations in the technological processes of the main production of natural leather, primary processing of raw materials, and industrial waste disposal have been identified. It has been established that the reasonable use of enzymes at different stages of the technological cycle of processing leather materials contributes to the manufacture of competitive products with a more careful attitude to raw materials, material and energy resources, and the ecological state of the environment.